Anakinra as Rescue Therapy to Treat Patients with Severe COVID-19 Refractory to Tocilizumab - Alijotas-Reig, Jaume; Esteve-Valverde, Enrique; Ruiz-Hidalgo, Domingo; López-Sánchez, Gabriel; Trapé-Pujol, Jaume; Miró-Mur, Francesc (Archives of Clinical and Biomedical Research, 2021)
Objective To evaluate the role played by anakinra in the treatment of patients with severe COVID-19 who fails to “accepted” standard of care and tocilizumab. Methods We conducted a retrospective cohort study assessed in Althaia Health Network University and Vall d’Hebrón University Hospital, in Barcelona, Spain. We included patients with confirmed RT-PCR for SARS-CoV-2, moderate-to-severe acute respiratory distress syndrome [PaO2:FiO2] (PAFI) ≤200 mmHg, and hyperinflammation. All of them were primarily managed with non-invasive ventilation outside of the ICU and received standard of care with hydroxy chloroquine, lopinavir/ritonavir, azithromycin, and enoxaparin supplemented with tocilizumab. These patients received an additional administration of 100 mg subcutaneous anakinra twice a day (low-dose) or every 6-8 hours (medium-dose). Mechanical ventilation-free survival, ICU admission, respiratory function changes (PAFI), inflammatory markers, and survival were analysed. Results Clinical and respiratory improvements were already present at 48 hours post-anakinra. PAFI increased 105.2% at 48 hours over anakinra administration and 166.9% at day 7. Respiratory function improvement was significant at day 7 (p<0.0001) with 10/12 (83%) responders having a PAFI ≥ 200 mm Hg. Despite of this improvement, inflammatory markers lasted to decrease. Two patients required ICU and temporary mechanical ventilation. No patients died and no adverse effects related to anakinra appeared. Short-time follow-up showed no relapses. Conclusion In severe ARDS related to SARS-CoV-2 refractory to standard of care plus tocilizumab, low-to-moderate doses of anakinra as a rescue therapy showed effectiveness and safety, avoiding mechanical ventilation and deaths.